Asuhan Keperawatan Pada Pasien Combustio Dengan Intervensi Pemberian Aromaterapi Lavender Terhadap Penurunan Tingkat Nyeri di Ruang Anggrek C RSUD Kabupaten Tangerang - Mugiyanto Mugiyanto; Cicirosnita J.Idu; Ahmad Hambali (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Background: Combustio or burns are damage to the skin or tissue that can occur due to contact of body parts with objects such as fire, hot liquids, electricity, chemicals and radiation. Combustio is still a serious case in Indonesia causing millions of people to die, namely more than 265,000 people every year. A non-pharmacological treatment that can be done to reduce pain in post-debridement burn wounds is giving lavender aromatherapy. Lavender aromatherapy is an aromatherapy in which the content of linalyl acetate and linalool can stimulate the release of endorphin hormones so that it can have a relaxing effect and is thought to help overcome discomfort disorders such as anxiety, can lower blood pressure and also pain. Method: The method used in this research is a descriptive method with a case study approach. Results: After the intervention of giving lavender aromatherapy using a diffuser for 3 days, the result was a decrease in pain in combustio post debridement surgery patients which was carried out every Monday and Thursday in the operating room with complaints of decreased pain, pain scale: 1, the patient looked relaxed and in the Paired Sample t-Test with a significance level α: 0.05, the results of data processing obtained a sig. (2-tailed) of 0.02. Conclusion: Lavender aromatherapy can reduce the level of pain during post-operative debridement combustio.